PROMOSI YANG KUAT: BAGAIMANA @ENGLISHNESIA MEMANFAATKAN INSTAGRAM DALAM KOMUNIKASI BISNIS - Nurul Aini; Cecep Safa’atul Barkah; Nurillah Jamil Achmawati Novel; Iwan Sukoco (Business Administration Department - Universitas Katolik Parahyangan, 2024)
The rapid development of information technology has made a tool called social media familiar to all people. Not only used as a daily communication tool, but social media can also be a tool for online business communication. Driven by information technology, marketing is now transformed into an online form through social media, such as Instagram. One of the businesses that uses Instagram for customer communication and marketing is @englishnesia. The research is meant to describe the systematic use of Instagram as a platform for communication on @englishnesia. This research applies a qualitative method and literature study with descriptive analysis and bibliographic annotations. @englishnesia utilizes several platforms, namely website, WhatsApp, and Instagram, as promotional media for online English courses. Digital marketing conducted by @englishnesia is analysed using the 7C elements and has fulfilled six of the seven digital marketing elements. The element that’s not fulfilled is customization due to limited features on Instagram social media. Nevertheless, the other elements have been used well, creating excellent communication between @englishnesia and its audience.